Jokowi’s Generals, Civilian Control, and the Power of the Panglima - Natalie Sambhi (Journal Of Global Strategic Studies, 2023)
The relationship between the president and the military chief (known as the Panglima) can be a useful proxy for understanding the state of civil-military relations in Indonesia. This research note argues that, under President Joko Widodo, democratic norms of civil-military relations have been further eroded with the selection of the Panglima becoming increasingly politicised, rather than being guided by operational or service rotation needs. Also, the president has experienced varying levels of civilian control over the military chief, influenced by factors such as personality and timing.